Globular cluster formation and evolution in the context of cosmological galaxy assembly: open questions - Forbes, Duncan A.; Kruijssen, Diederik (Arxiv, 2018)
We discuss some of the key open questions regarding the formation and evolution of globular clusters (GCs) during galaxy formation and assembly within a cosmological framework. The current state-of-the-art for both observations and simulations is described, and we briefly mention directions for future research. The oldest GCs have ages $\ge$ 12.5 Gyr and formed around the time of reionisation. Resolved colour-magnitude diagrams of Milky Way GCs and direct imaging of lensed proto-GCs at z $\sim$ 6 with JWST promise further insight. Globular clusters are known to host multiple populations of stars with variations in their chemical abundances. Recently, such multiple populations have been detected in $\si
Artikelversion: 31. Januar 2018
Gesehen am 19.032018